Reducing Electronic Transport Dimension to Topological Hinge States by Increasing Geometry Size of Dirac Semimetal Josephson Junctions - Li, Cai-Zhen; Wang, An-Qi; Li, Chuan; Zheng, Wen-Zhuang; Brinkman, Alexander; Yu, Da-Peng; Liao, Zhi-Min (Physical review letters, 2020)
The notion of topological phases has been extended to higher-order and has been generalized to different dimensions. As a paradigm, Cd_{3}As_{2} is predicted to be a higher-order topological semimetal, possessing three-dimensional bulk Dirac fermions, two-dimensional Fermi arcs, and one-dimensional hinge states. These topological states have different characteristic length scales in electronic transport, allowing one to distinguish their properties when changing sample size. Here, we report an anomalous dimensional reduction of supercurrent transport by increasing the size of Dirac semimetal Cd_{3}As_{2}-based Josephson junctions. An evolution of the supercurrent quantum interferences from a standard Fraunhofer pattern to a superconducting quantum interference device (SQUID)-like one is observed when the junction channel length is increased. The SQUID-like interference pattern indicates the supercurrent flowing through the 1D hinges. The identification of 1D hinge states should be valuable for deeper understanding of the higher-order topological phase in a 3D Dirac semimetal.